Cross-dressing and Empowerment in Anglo-Indian Fiction:Embracing Subaltern Invisibility - Jaine CHEMMACHERY (E-REA)
In several works of colonial fiction, British characters adopt disguise to escape a potentially dangerous situation or simply to have access to places ordinarily closed to members of the colonizer society. The police officer Strickland, in Rudyard Kipling’s short stories, often dresses as an Indian man to get keener knowledge of Indian customs while escaping the British system of surveillance. In another story by Kipling, “His Wedded Wife” (1887), a British soldier, often bullied by his masculine fellow-soldiers, once impersonates his officer’s wife so efficiently that gender passing finally earns him the respect of his companions. In many colonial stories, the adoption by cross-dressers of a subaltern persona, in terms of race, class and/or gender, is part of a strategy of empowerment. Drawing on the concept of “subalternity” (Guha 1982), I want to study the parallel between gender passing and racial passing as regards empowerment in colonial fiction since the two challenge the notions of stable subject-positions. In the wake of “spectrality studies”, one may also wonder about the modalities underlying the visible paradox between empowerment, invisibility and subalternity in colonial fiction. How is one to get more agency by adopting the traits of figures known to be in a situation of minority, and as such, of presumed invisibility? How can subaltern invisibility become a site of empowerment?